Determination of warm, sensitive permafrost areas in near‐vertical rockwalls and evaluation of distributed models by electrical resistivity tomography. Issue 5 (9th May 2015) - Magnin, Florence; Krautblatter, Michael; Deline, Philip; Ravanel, Ludovic; Malet, Emmanuel; Bevington, Alexandre
Abstract Alpine rockwalls with warm permafrost (near 0°C) are the most active rockfall detachment zones in the Mont Blanc massif (MBM, French Alps) with more than 380 recent events. Near‐vertical rockwall permafrost is spatially controlled by variations in rock fractures, snow cover, and microtopography. A reliable method to validate the distribution of permafrost in critical and unstable areas does not yet exist. We present seven electrical resistivity tomography (ERT) surveys measured on five near‐vertical rockwalls in the MBM from 2012 and 2013 that have been calibrated with measurements on a granite sample in the laboratory. ERT shows consistent measurements of remaining sensitive permafrost relating to inferred temperatures from 0 to −1.5°C. ERT results demonstrate evidence of topographic controls on permafrost distribution and resistivity gradients that appear to reflect crest width. ERT results are compared to two permafrost index maps that use topoclimatic factors and combine effects of thin snow and fractures, where index model spatial resolution is crucial for the validation with ERT. In cryospheric environments, index maps seem to overestimate permafrost conditions in glacial environments. As a consequence, the sensitive areas of permafrost may slightly deviate from the results from distributed models that are only constrained by topoclimatic factors and interpreted with consideration of local fracture and snow conditions. This study demonstrates (i) that the sensitive and hazardous areas of permafrost in near‐vertical rock faces can be assessed and monitored by the means of temperature‐calibrated ERT and (ii) that ERT can be used for distributed model validation.